2012
DOI: 10.1097/inf.0b013e318266bcf9
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Coronary Artery Abnormalities

Abstract: The majority of CA abnormalities in children with KD were identified in the initial ECHO, during the first week of illness. Earlier diagnosis and treatment is needed to impact the incidence of CA abnormalities in children with KD. Increased clinical suspicion and earlier use of ECHO in the initial workup of children with suspected KD may lead to more rapid diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 20 publications
4
32
1
1
Order By: Relevance
“…In up to 80% of those patients who have significant dilation or aneurysms as noted on later echocardiograms, some abnormality is evident on the initial baseline echocardiogram obtained in the first 10 days of illness. 128 The largest proportion of patients with coronary artery abnormalities will have dilation only, characterized by luminal measurements outside the normal range but with a maximal Z score of <2.5. Dilation resolves within 4 to 8 weeks in the majority.…”
Section: Coronary Artery Abnormalitiesmentioning
confidence: 99%
“…In up to 80% of those patients who have significant dilation or aneurysms as noted on later echocardiograms, some abnormality is evident on the initial baseline echocardiogram obtained in the first 10 days of illness. 128 The largest proportion of patients with coronary artery abnormalities will have dilation only, characterized by luminal measurements outside the normal range but with a maximal Z score of <2.5. Dilation resolves within 4 to 8 weeks in the majority.…”
Section: Coronary Artery Abnormalitiesmentioning
confidence: 99%
“…A recent study reported that 81% of patients with KD who eventually developed coronary aneurysms showed coronary abnormalities on their initial echocardiograms [12]. Studies have proposed the use of adjuvant therapies with agents such as atorvastatin [13], steroids [14, 15], and dalteparin [16] to ameliorate the CALs of patients with KD during the acute KD phase.…”
Section: Discussionmentioning
confidence: 99%
“…A delay of management may be induced by postponing diagnosis of incomplete presentations until coronary artery abnormality is confirmed. It is now recognized that a large number of patients with KD do not fulfill full clinical KD criteria (i.e., incomplete KD) and that up to 20% of patients who are treated for KD are incomplete cases5,14,37,38).…”
Section: What Does Incomplete Kd In Infants Mean?mentioning
confidence: 99%